Changing the Conversation, Why We Need to Reframe Corruption as a Public Health Issue; Comment on "We Need to Talk About Corruption in Health Systems" - David Clarke (Kerman University of Medical Sciences, 2020)
There has been slow progress with finding practical solutions to health systems corruption, a topic that has long languished in policy-makers "too difficult tray." Efforts to achieve universal health coverage (UHC) provide a new imperative for addressing the long-standing problem of corruption in health systems making fighting corruption at all levels and in all its forms a priority. In response, health system corruption should be classified as a risk to public health and addressed by adopting a public health approach. Taking a public health approach to health systems corruption could promote a new paradigm for working on health system anti-corruption efforts. A public health approach could increase the space for policy dialogue about corruption, focus work to address corruption on prevention, help generate and disseminate evidence about effective interventions strategies, and because of its focus on multisectoral action would provide new opportunities for promoting cooperation on anti-corruption work across multiple agencies and sectors. Using a public health approach to tackle health system corruption could help address the current inertia around the topic and create a new positive mindset among policy-makers who would come to see corruption as a manageable public health problem rather than an intractable one.